A model for analysing data portal performance: The biodiversity case - Corrêa, Pedro Luiz Pizzigatti; Salvanha, Pablo; Saraiva, Antonio Mauro; Scarpelini Neto, Paulo [UNESP]; Valêncio, Carlos Roberto [UNESP]; Souza, Rogéria Cristiane Gratão de [UNESP] (My University, 2013)
Currently, many museums, botanic gardens and herbariums keep data of biological collections and using computational tools researchers digitalize and provide access to their data using data portals. The replication of databases in portals can be accomplished through the use of protocols and data schema. However, the implementation of this solution demands a large amount of time, concerning both the transfer of fragments of data and processing data within the portal. With the growth of data digitalization in institutions, this scenario tends to be increasingly exacerbated, making it hard to maintain the records updated on the portals. As an original contribution, this research proposes analysing the data replication process to evaluate the performance of portals. The Inter-American Biodiversity Information Network (IABIN) biodiversity data portal of pollinators was used as a study case, which supports both situations: conventional data replication of records of specimen occurrences and interactions between them. With the results of this research, it is possible to simulate a situation before its implementation, thus predicting the performance of replication operations. Additionally, these results may contribute to future improvements to this process, in order to decrease the time required to make the data available in portals. © Rinton Press.
Keywords: Data portal performance; Data replication processes; Distributed database systems; Biodiversity datum; Biological collections; Computational tools; Data portal; Data replication; Future improvements; Information networks; Large amounts; Biodiversity; Database systems; Information services; Research; Data handling